The Influence of Stock Market Anomalies on Sharia Stock Returns in Companies Implementing the ESG (Environmental, Social, and Governance) Concept in Indonesia - Eva Syahrida Siregar; Maryam Batubara; Nur Ahmadi Bi Rahmani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Market anomaly is a deviation that occurs in the capital market. The existence of market anomalies (irregularities) then forms one of the phenomena that disrupts the efficient capital market hypothesis theory. This market anomaly rejects the hypothesis of the capital market efficiency concept which states that investors cannot predict prices and rates of return based on past stock prices due to random returns, but can be predicted based on the influence of the calendar or a certain period. So that this seasonal anomaly can be utilized by investors to obtain high abnormal returns. This study was conducted to test the effect of the Monday Effect and Ramadhan Effect phenomena on the returns of companies that apply the ESG concept in Indonesia for the period 2024. The sampling technique used in this study uses NonProbability Sampling, namely quota sampling. Data analysis was carried out using descriptive analysis and hypothesis testing. The results of the analysis show that there is no Monday Effect and Ramadhan Effect phenomenon in Indonesia in 2024. So the Monday Effect and Ramadhan Effect phenomena do not affect the returns of companies that apply the ESG concept in Indonesia